Bond strength test of acrylic artificial teeth with prosthetic base - Kurnikasari, Erna; Mahmud, Muslich; Dziab, Hasna (Padjadjaran Journal of Dentistry, 2008)
Denture consists of acrylic artificial teeth and acrylic prothesis base bond chemically with a bond strength of 315 kgF/cm2. Most of the commercial acrylic artificial teeth do not specify their specifications and all of those acrylic artificial teeth do not include mechanical data (bond strength). The aim of this study is to discover which acrylic artificial teeth meet ADA specification no. 15. This study is a descriptive analytic study performed to 5 acrylic artificial teeth posterior brands commonly used by dentists and technicians. From each brand, 3 sample teeth were taken. The acrylic artificial teeth were prepared into a rectangular shape and were attached between acrylic prothesis base simulation and jigs. The sample was given tensile load using a Universal Testing Machine. The amount of force that causes the teeth to be fractured was recorded and the bond strength was calculated. The results of the study show that the average value for the five acrylic artificial teeth for the five brands were as followed: Brand A, 125.993 kgF/cm2; B, 188.457 kgF/cm2; C, 175.880 kgF/cm2; D, 153.373 kgF/cm2; E, 82.839 kgF/cm2. The data can be tested statistically by using One Way ANOVA test and Dunnett test (alpha = 0.05). From the study, it is concluded that the five acrylic artificial teeth have a bond strength below the ADA specification no. 15.